Extending the Minority Stress Model to Understand Mental Health Problems Experienced by the Autistic Population. (March 2020) - Botha, Monique; Frost, David M.
Research into autism and mental health has traditionally associated poor mental health and autism as inevitably linked. Other possible explanations for mental health problems among autistic populations have received little attention. As evidenced by the minority disability movement, autism is increasingly being considered part of the identities of autistic people. Autistic individuals thus constitute an identity-based minority and may be exposed to excess social stress as a result of disadvantaged and stigmatized social status. The authors test the utility of the minority stress model as an explanation for the experience of mental health problems within a sample of high-functioning autistic individuals ( n = 111). Minority stressors including everyday discrimination, internalized stigma, and concealment significantly predicted poorer mental health, despite controlling for general stress exposure. These results indicate the potential utility of minority stress in explaining increased mental health problems in autistic populations. Implications for research and clinical applications are discussed.